Performance of French Bean (Phaseolus vulgaris L.) Genotypes In Sylhet Region of Bangladesh (Bangladesh Agronomy Journal, 2016)
An experiment was conducted at farming system research and development (FSRD) site, Jalalpur and multi location testing (MLT) sites, Zokigonj and Moulvibazar during 2013-2015 to evaluate the suitable varieties (genotypes) of French bean for maximize the seed yield of the farmers. The experimental design was a randomized complete block (RCB) with 6 dispersed replications. Eight bush bean genotypes were tested of which 3 were developed by BARI (var. BARI Jharsheem-1, BARI Jharsheem-2, BARI Jharsheem-3), five local accessions: Local-1(black), Local-2 (white colour with chocolate spot at hylum), Local-3 (coffee colour), Local-4 (coffee colour with few chocolate spots) and Local-5 (black with chocolate colour spots). The seed yields were varied significantly among the genotypes. All the local French bean lines performed better and produced higher seed yields compared to BARI developed varieties. The maximum seed yields 2.66, 3.48 and 2.05 t ha-1 was produced by Local-4 and Local-5 at Jalalpur, Zakigonj and Moulvibazer, respectively. So, Local-4 and Local-5 variety as the most promising one due their relatively good plant vigor and high seed yield potentiality.Bangladesh Agron. J. 2016, 19(1): 37-44